2007
DOI: 10.1039/b704008c
|View full text |Cite
|
Sign up to set email alerts
|

Optical filtering technologies for integrated fluorescence sensors

Abstract: Numerous approaches have been taken to miniaturizing fluorescence sensing, which is a key capability for micro-total-analysis systems. This critical, comprehensive review focuses on the optical hardware required to attenuate excitation light while transmitting fluorescence. It summarizes, evaluates, and compares the various technologies, including filtering approaches such as interference filters and absorption filters and filterless approaches such as multicolor sensors and light-guiding elements. It presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
134
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 136 publications
1
134
0
1
Order By: Relevance
“…These filters contain multiple layers of different index materials which cause components of the light to reflect and destructively interfere with the incoming light. By precisely depositing these layers, sharp cut off frequencies can be achieved by such filters [5]. These filters also typically provide incredible high attenuation (OD E < 5).…”
Section: Spectral Separationmentioning
confidence: 99%
See 4 more Smart Citations
“…These filters contain multiple layers of different index materials which cause components of the light to reflect and destructively interfere with the incoming light. By precisely depositing these layers, sharp cut off frequencies can be achieved by such filters [5]. These filters also typically provide incredible high attenuation (OD E < 5).…”
Section: Spectral Separationmentioning
confidence: 99%
“…In confocal optical systems the LCE is dictated by the Numerical Aperture (NA) of the device optics [18]. In integrated devices, such as the one presented by Burns et al [41] where the detector is placed directly below the microfluidic channel, the LCE of Fluorescence (LCE F l ) is determined by the size of the detector and the distance between the detector and the channel [5]. By modelling the fluorescences as an isotropic source (as shown in Figure 2.3a) it can be shown that the LCE will follow the relationship shown in Eq.…”
Section: Geometric Separationmentioning
confidence: 99%
See 3 more Smart Citations